Considerações sobre a recepção da obra de Machado - Maria Antonieta Jordão de Oliveira Borba (Matraga, 2008)
This essay is a reflection on the critical reception of Machado de Assis’ works, taking into account some theoretical presuppositions implied in the interpretations of the writer’s production. The essay discusses some of the late 19th-century views about the role played by Brazilian intellectuals and politicians as opposed to the one assumed by Machado as an author of fictional narratives. Besides, the essay investigates the aesthetic issues which emerge when the expression literary “realism” is taken into consideration. Some critical articles will be discussed, as far as they make major contributions to the study of the Brazilian writer’s fictional strategies.